2014
DOI: 10.1051/parasite/2014035
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in broiler chickens in Zhejiang Province, China: molecular characterization of oocysts detected in fecal samples

Abstract: Cryptosporidium is one of the most important parasites in poultry, and this pathogen can infect more than 30 avian species. The present study investigated the infection rate of Cryptosporidium among broiler chicken flocks. A total of 385 fecal samples from broiler chickens in 7 regions of Zhejiang Province collected from November 2010 to January 2012 were examined by microscopy. Thirty-eight (10%) samples were positive for Cryptosporidium infection, and 3 genotypes (Cryptosporidium baileyi, Cryptosporidium mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
4
31
1
4
Order By: Relevance
“…In the present study, C. meleagridis was detected in 9-63% of chicken broilers. Wang et al (2014) reported a much lower prevalence (less than 2%) of C. meleagridis in chickens. In contrast, other authors reported C. meleagridis in 35-44% of turkeys (Pavlásek 1994, Gharagozlou et al 2006, Baroudi et al 2013.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, C. meleagridis was detected in 9-63% of chicken broilers. Wang et al (2014) reported a much lower prevalence (less than 2%) of C. meleagridis in chickens. In contrast, other authors reported C. meleagridis in 35-44% of turkeys (Pavlásek 1994, Gharagozlou et al 2006, Baroudi et al 2013.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies performed outside Brazil affirm that infections by C. baileyi, C. galli and other parasite genotypes are present in several avian cases. While the number of reports of infection by C. meleagridis was low (SRÉTER & VARGA, 2000;WANG et al, 2014), Ng et al (2006) did not find this species in 430 avian fecal samples, and described that C. meleagridis infection has low prevalence in avian hosts. This finding is the opposite what we observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the 18S rRNA n-PCR reactions were positive for Cryptosporidium spp. in 91 (25.9%) of 351 fecal samples There are few reports of Cryptosporidium molecular characterization from chickens in Brazil (HUBER et al, 2007;NAKAMURA et al, 2009) and worldwide (HSU et al, 2008;NG et al, 2006;SILVERLÅS et al, 2012;WANG et al, 2014), however, none of the previously studies reported studies worked with free-range chickens. In Brazil, Huber et al (2007) and Nakamura et al (2009) worked with chickens from indoor public markets and chickens under captivity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although Wang et al (2014b) reported the presence of avian genotype II in 0.78% (3/385) of fecal samples from chickens in China, Meireles et al (2006) did not observe infection among chickens that were experimentally infected with avian genotype II and screened for Cryptosporidium infection using cytology, histology and oocyst screening in feces.…”
Section: Proventriculusmentioning
confidence: 97%
“…In Algeria, a report showed a high prevalence of C. meleagridis: 34% (26/90) in chickens and 44% (25/57) in turkeys (BAROUDI et al, 2013). However, in China, a low prevalence was described for C. meleagridis among broiler chickens (0.52%; 2/385) (WANG et al, 2014b), laying hens (0.19%; 3/1542) (WANG et al, 2010) and quails (0.22%; 4/1818) . Li et al (2012) found C. meleagridis in 24.4% (22/90) of the wastewater samples collected from four cities in China.…”
Section: Importance For Public Healthmentioning
confidence: 99%